Applied modelization to electricity markets, as a financially unstable complex system (2016)
The challenges faced by different sectors of the economy, respond to the evolution and specialization of consumers and producers, where the needs are becoming more complex. In this sense, during the last 5 years the electricity markets have undergone an evolutionary pro- cess that aims to meet the needs of all stakeholders in the midst of sustainability scenarios. Thus, the agents involved in the electricity market, present a num- ber of exhibitions of operational nature, legal, ethical, financial, among others, which require a specialization allowing the entry of new tech- nologies. This research project focuses on the study of financial risk, which despite being so specific, consider many elements with the aim of ensuring the functioning of the market and its participants. In previous studies, some models have concentrated on the in- vestigation of blackouts phenomena, the stability of the network, the dynamic power system, and Smart grids, among others. Mean- while other investigations have addressed the problem of forecasting different variables like the spot price and corporate strategy, with the aim of increasing the profitability of the participants. Now, this project presents the proposal of a complex financial model, which results in calculating a market equilibrium considering initial condi- tions and risk constraints. Using game theory it demonstrates equi- librium instability and that through complexity it is possible to find an optimal scenario in terms of profitability for the system and the agents. In chapter 1 it carried out a review of previous studies in order to justify the investigation, then Chapter 2 includes a description of the Colombian electricity market, with different specifications. In chap- ter 3 the KRI are defined, and they will be integrated in Chapter 4 as a fundamental part of the comprehensive model. Finally, Chapter 5 includes the results of the study ending with some possible further studies and additional considerations.